SYN-EXHUMATION PERVASIVE BRITTLE DEFORMATION IN THE VOLTRI (NW ITALY) SERPENTINITE: THE CHRYSOTILE-CEMENTED ACQUASANTA BRECCIA - Barale, Luca; Piana, Fabrizio; Avataneo, Chiara; Botta, Serena; Capitani, Giancarlo; Cossio, Roberto; Marcelli, Igor; Petriglieri, Jasmine Rita; Tallone, Sergio; Turci, Francesco; et al. (Ofioliti, 2023)
This paper sheds light on syn-exhumation, pervasive cataclastic processes occurred on competent serpentinites of a metaophiolitic sub-unit of the Voltri Massif. The reported data highlight the importance of the compositional and structural heterogeneities within the ophiolite-bearing exhumation channels, since the observed pervasive cataclastic processes affected only the more competent rock bodies of the metaophiolitic unit, giving origin to a serpentinite breccia, named as Acquasanta Breccia. This breccia is cemented by random-oriented chrysotile fibers that give rise to a very uncommon microstructure, as highlighted by optical microscopy, Micro-Raman spectroscopy, SEM-EDS and TEM investigations. The Acquasanta Breccia underwent a sequence of syn-exhumation tectonic events, accompanied by the onset of different generations and types of chrysotile, which occur both in veins and in the rock matrix. The breccia records the intermediate and late stages of the exhumation of the Voltri meta-ophiolites, which occurred after the development of the retrograde greenschist-facies foliation and before the late shallower faulting events.